Pseudo-monotonicity and degenerate elliptic operators of second order - Youssef Akdim (Electronic Journal of Differential Equations, 2002)
Extending the theory of pseudo-monotone mappings in weighted Sobolev spaces, we prove some existence results for degenerate or singular elliptic equations generated by the second-order differential operator $$ Au(x)=-mathopm diva(x,u,abla u))+a_0(x,u,abla u), $$ (in particular, when only large monotonicity is satisfied)